Spin fluctuations and the "strange metal" behavior of a weakly doped antiferromagnet - Loktev, V.M.; Turkowski, V. (Condensed Matter Physics, 2008)
We analyze the spectral properties of a phenomenological model for a weakly doped two-dimensional antiferromagnet,
in which the carriers move within one of the two sublattices where they were introduced. Such a
constraint results in the free carrier spectra with the maxima at k = (±π/2,±π/2) observed in some cuprates.
We consider the spectral properties of the model by taking into account uctuations of the spins in the antiferromagnetic
background. We show that such fluctuations lead to a non-pole-like structure of the single-hole
Green's function and these fluctuations can be responsible for some anomalous strange metal properties of
underdoped cuprates in the nonsuperconducting regime. Проаналiзовано спектральнi властивостi феноменологiчної моделi для слабо легованого двовимiрного антиферомагнетика, в якому носiї рухаються у саме тiй з двох пiдграток, куди вони були введенi. Таке обмеження приводить до спектрiв вiльних носiїв з максимумами при k = (±π/2,±π/2), що спостерiгаються у деяких купратах. Спектральнi властивостi моделi дослiджено шляхом врахування флуктуацiй спiнiв вiдносно антиферомагнiтного фону. Показано, що такi флуктуацiї ведуть до безполюсної структури однодiркових функцiй Ґрiна, а також цi флуктуацiї можуть вiдповiдати за певнi аномальнi властивостi недолегованих купратiв типу “дивного металу” у ненадпровiдному режимi.